2006
DOI: 10.1021/bi061662p
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Four Covalently-Linked Yeast Cytochrome c/Cytochrome c Peroxidase Complexes:  Evidence for Electrostatic Interaction between Bound Cytochrome c Molecules

Abstract: Four covalent complexes between recombinant yeast cytochrome c and cytochrome c peroxidase (rCcP) were synthesized via disulfide bond formation using specifically designed protein mutants [Papa, H. S., and Poulos, T.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…However, in the extreme case of this rigid limit, if the site constants were equal to the measured thermodynamic affinity constants (K 1 ≈ K I and K 2 ≈ K II ), then repulsion would be zero, and this is ruled out by the measurements of Erman and coworkers, 42 as noted above. This requires that the actual site-binding constant K 2 must be larger than the measured value of K II = 10 4 , although still enough smaller than K 1 that the binary is predominantly in the tightly-binding form in accordance with the NMR studies.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, in the extreme case of this rigid limit, if the site constants were equal to the measured thermodynamic affinity constants (K 1 ≈ K I and K 2 ≈ K II ), then repulsion would be zero, and this is ruled out by the measurements of Erman and coworkers, 42 as noted above. This requires that the actual site-binding constant K 2 must be larger than the measured value of K II = 10 4 , although still enough smaller than K 1 that the binary is predominantly in the tightly-binding form in accordance with the NMR studies.…”
Section: Discussionmentioning
confidence: 94%
“…In fact, calculations and experiments have confirmed that the two Cc cannot bind independently, and that the stability of the ternary is diminished by electrostatic repulsions between the two positively charged Cc (anti-cooperative binding). 41, 42 …”
Section: Discussionmentioning
confidence: 99%
“…5a ). Previous experimental studies suggested that electrostatic repulsion between two Cc molecules in the ternary complex accounts for the drastic difference in the affinity constants for the first and second binding steps 37 38 39 . Difference in binding energies for the high- and low-affinity sites (ΔΔ G ) provides the upper limit for the electrostatic repulsion energy (Δ G Φ ), a presumed dominant term in the energy penalty for such ‘anticooperative' binding.…”
Section: Resultsmentioning
confidence: 99%
“…This hypothesis is supported by the cytochrome c/CcP cross-linking studies of Poulos and coworkers (28,45,46) as well as those of Nakani and colleagues (29,30). Pappa and Poulos (45) and Papa et al (46) used site-directed mutagenesis to engineer specific cysteine residues into both yeast cytochrome c and CcP to covalently attach cytochrome c to the Pelletier/Kraut binding site through a CcP Cys-290/cytochrome c Cys-73 disulfide bond.…”
Section: Relation To Other Studiesmentioning
confidence: 86%